The Recurrent Eclipsing Nova U Sco: A Short Review - R. González-Riestra (Acta Polytechnica CTU Proceedings)
U Scorpii is the recurrent nova with the shortest inter-outburst period, only ten years. The last active phase took place at the beginning of 2010, and it provided a large amount of data from both ground-based and space observatories. This paper reviews some of the more relevant recent findings and points out some, still unanswered, questions.